Rancang Bangun Circulating System Water Heater dengan Sumber Panas Solar Cell - Harpen, Romario Van; Purwantono, Purwantono; Syahri, Budi; Wulansari, Rizky Ema (ARZUSIN, 2023)
The use of solar energy is very important to increase today because solar energy is renewable energy and also does not cause pollution, but solar collector equipment is still needed to convert solar energy into heat energy. This study aims to analyze the heat transfer in the flat plate solar collector which is used as a source of thermal energy in the water heating process for bathing. A solar collector is used to absorb solar thermal energy and then transfer it to a water pipe. The pipe material uses copper which has a very high conductivity value with an outer diameter of 5/8 '' (15.7 mm). The collector plate uses aluminum plates, because aluminum plates are quite high heat conductors. The dimensions of the box / collector frame are 150 cm long, 80 cm wide and 80 cm high. The collector frame is made of steel, with an angle of 15 ˚ of the tool. The results of the study in sunny weather conditions 46.8 c, then the results in the form of sunny cloudy weather produce an outflow water temperature of 44.3 c and finally the results data collection in the form of cloudy weather the results obtained are 38.3 c. Based on the experimental process, the collector temperature was taken using a thermocouple,heat the water to the initial temperature in a bucket of 28˚c and the temperature of the water out during the study to produce 40˚c.